Kunst nach Kunst - Adorf, Sigrid; Billows, Carmen; Boulboullé, Guido; Bovier, Lionel; Clauss, Ingo; Conzen-Meairs, Ina; Deecke, Thomas; Fischer, Bianca; Friese, Peter; Goldenstein, Uwe; Gorissen, Mascha; Guenther, Bruce; et al. (Bremen : Hauschild Verlag, 2002)
Andre, Carl ; Armleder, John ; Art & Language ; Bär, Holger ; Baldessari, John ; Benglis, Lynda ; Stoltmann, Kirsten ; Durham, Jimmie ; General Idea ; Graham, Rodney ; Hastings, Gail ; Indiana, Robert ; Isaacs, John ; Judd, Donald ; Kippenberger, Martin ; Lachowicz, Rachel ; Latham, John ; Lavier, Bertrand ; LeWitt, Sol ; Locher, Thomas ; Majerus, Michel ; McCarthy, Paul ; Monk, Jonathan ; Nicolai, Olaf ; Oehlen, Albert ; Pollock, Jackson ; Pop, Susi ; Pusenkoff, George ; Rauschenberg, Robert ; Richter, Daniel ; Schneyder, C. ; Smith, Bob & Roberta ; Sturtevant ; Takeoka, Yuji ; Tasset, Tony ; Tillers, Imants ; Uklanski, Piotr ; Wohnseifer, Johannes ; Zimmermann, Peter ; Zobernig, Heimo
biog., bibliog. p. 211-219
Duits
Engels
Kunst nach Kunst / Art after Art, Weserburg Museum für moderne kunst Bremen, 2002
boek